Survei Kepuasan Siswa Terhadap Sistem Pembelajaran di Sekolah Berbasis WEB - Sapri, Sapri; Asnawati, Asnawati; Sari, Dian Mardiati; Trianggana, Dimas Auli; Kurnianto, Ridho Rahman (Universitas Dehasen Bengkulu, 2023)
The aim of this research is to assess student satisfaction with the learning system at SMA Negeri 6 Kepahiang. The survey method was used to collect data from students at SMA Negeri 6 Kepahiang. The sample for this research consisted of 100 students selected randomly. The research instrument is a questionnaire containing 8 items which assess opinions regarding the teacher's presence, regarding the teacher's competency/ability, regarding the teacher's learning system in the classroom, the teacher's responsiveness in explaining and answering questions, the teacher's concern for students in the class, the infrastructure and facilities used, The teacher's delivery of learning is in accordance with the learning design, and your opinion on the communication provided by the teacher in class.The research results show that the majority of students are satisfied with the learning system at SMA Negeri 6 Kepahiang. However, there are several aspects that need to be improved, such as the quality of facilities and interaction between teachers and students. Apart from that, some students also feel dissatisfied with the learning atmosphere at SMA Negeri 6 Kepahiang. This research can provide important information for schools to improve the quality of learning systems and meet students' needs in teaching and learning